Bridging the Gap in Interactive Education: A WordWall Training Initiative for MGMP Instructors in Padang Panjang - Agustina, Dina (Pelita Eksakta, 2024)
In the quest for educational advancement in Padang Panjang, Indonesia, this article presents a groundbreaking initiative titled "Bridging the Gap in Interactive Education: A WordWall Training Initiative for MGMP Instructors." The primary objective of this initiative was to elevate interactive teaching methodologies among MGMP (Mata Pelajaran Guru) instructors by focusing on three crucial assessment indicators: the enhancement of knowledge regarding instructional media, the cultivation of proficiency in utilizing teaching media throughout the learning process, and the introduction of innovative tools and insights applicable to the teaching process. Conducted with active participation from MGMP instructors, this training program centered around WordWall, a digital educational platform. The remarkable outcome of this study reveals unanimous agreement, with all participating instructors unequivocally affirming their satisfaction with the improvements in the assessed indicators. These results signify the effective bridging of the gap in interactive education by offering professional development opportunities and introducing novel tools, such as WordWall. This initiative serves as a pivotal step in empowering instructors and elevating the quality of education in Padang Panjang, underscoring the importance of embracing innovative teaching methodologies for a brighter educational future.